2012
DOI: 10.4236/abb.2012.38135
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of Norway spruce clones regarding their natural durability, physical and chemical properties

Abstract: Genetic variation of ten Norway spruce (<i>Picea abies</i> (L.) Karst.) clones regarding their decay resistance against brown rot fungi, as well as physical and chemical properties of clones were investigated. 31- year-old spruce clones: 26, 31, A10, A15, A7, B10, B15, B6, V7, V9 were selected across Latvia. The stem diameters of spruce clones varied between 13.0 and 20.9 cm. The wood density of clones ranged from 361 to 443 kg/m<sup>3</sup>. Klason lignin content, depending on the clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…According to Swedish study, authors in Picea abies reported tracheid lengths to be 1.3 mm for JW, and 2.5 to 3mm in MW [17]. According to Latvian study, 31-years-old clones of Picea abies have a mean length of tracheids 2.4±0.2 mm and mean width of tracheids 31.7±1.5µm [18]. Similar results were found in 24-year-old Picea sitchensis trees come from region of British Columbia, Canada with a mean length of tracheids approx.…”
Section: Characteristics Of Jwmentioning
confidence: 99%
“…According to Swedish study, authors in Picea abies reported tracheid lengths to be 1.3 mm for JW, and 2.5 to 3mm in MW [17]. According to Latvian study, 31-years-old clones of Picea abies have a mean length of tracheids 2.4±0.2 mm and mean width of tracheids 31.7±1.5µm [18]. Similar results were found in 24-year-old Picea sitchensis trees come from region of British Columbia, Canada with a mean length of tracheids approx.…”
Section: Characteristics Of Jwmentioning
confidence: 99%
“…(vi) Structural use -the suitability of wood in internal or external structures is directly related to its natural durability, which depends on its anatomical structure and chemical composition (Irbe et al 2012). Wood with high percentage of parenchyma tends to have lower natural durability.…”
Section: Discussionmentioning
confidence: 99%
“…this feature is readily observable in the images obtained using transmission electron microscopy (tEM) of ultrathin sections stained with potassium permanganate (KMnO 4 ), a reagent widely used to contrast lignin in ultrastructural studies of secondary xylem, including wood. While UV microscopy may be considered the most appropriate and reliable method for detecting lignin at the microscopic level (Koch & Kleist 2001;Schmitt et al 2006;Irbe et al 2012), tEM microanalysis of wood samples after the lignin has been chemically marked with either Br or Hg is probably the most accurate high resolution and quantitative method available combining morphology at both low and high magnifications with chemical specificity (Eriksson et al 1988;Daniel & Nilsson 1987;Daniel et al 1991).…”
Section: Introductionmentioning
confidence: 99%